Enhancing Work Performance of Senior Employees in the Shipping Department: A Case Study of a Private Company - โพธิ์เกษม, ภนิดา; ตั้งเด่นชัย, พิศุทธิ์; กาวิชา, ศิริวรรณ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This research aims to improve the work performance of senior employees in the shipping department through a case study of a private company. The study focuses on identifying the work-related issues faced by senior employees, particularly in reducing errors and delays in document retrieval, as well as shortening the working time in the product shipping process. Data was collected between April and June 2025. The findings revealed that the workflow in the shipping department contained waste and discontinuities, leading to delays and errors in product shipments. Using the 5W1H Analytical thinking the issues, the research team developed an improvement plan based on the ECRS (Eliminate Combine Rearrange Simplify) concept, which included consolidating steps that could be performed simultaneously, reorganizing the workflow, and improving other procedures. Additionally, visual control was implemented through signage to facilitate faster and easier document retrieval. As a result of the process improvements, the working time was reduced by approximately 65 minutes, the number of steps causing waste decreased from 12 to 10, overtime hours were reduced by 29.87%, and work errors were reduced by 20%, leading to increased work efficiency among employees.